Cover Feature: Upcycling Plastic Wastes into Value‐Added Products by Heterogeneous Catalysis (ChemSusChem 14/2022). Issue 14 (5th July 2022) - Tan, Tian; Wang, Wei; Zhang, Kai; Zhan, Zixiang; Deng, Weiping; Zhang, Qinghong; Wang, Ye
Abstract : The Cover Feature shows the upcycling of various plastic wastes such as polyethylene (PE), polyethylene terephthalate (PET), and polylactic acid (PLA) into high‐value chemicals, lubricants, fuels, and carbon materials. Heterogeneous catalysis plays a determining role in the product distribution and reaction efficiency. More information can be found in the Review by T. Tan et al .